シラセ コウロ (1984-1985) ニ オケル ヒョウメン オヨビ センテイ カイスイ チュウ ノ クロロフィル α リョウ - 福田, 靖; フクダ, ヤスシ; 大野, 正夫; オオノ, マサオ; 岩波, 圭祐; イワナミ, ケイスケ; 當重, 弘; トウジュウ, ヒロシ; Fukuda, Yasushi; Ohno, Masao; Iwanami, Keisuke; Touju, Hiroshi (1986)
P(論文) 1984年11月から1985年4月まで第26次南極地域観測隊による海洋生物定常観測の一環として, 「しらせ」航路上に沿って表面海水中(バケツ採水)および亜表面海水中(船底からのポンプ採水, 水深約8m)のクロロフィルa量を測定した。表面海水と亜表面海水中のクロロフィルa量の値は, 全測定値の平均値で比較すると, 前者で0.01mg/m^3高かった。しかし, 両深度におけるクロロフィル濃度の変動のしかたは全航海を通して同じ傾向を示し, 両者間にはきわめて高い正の相関が認められた。南大洋のクロロフィルa濃度は12月上旬, 東経110度線上に沿った南下航路上において, オーストラリア亜南極前線と南極収束線の間で最大値1.51mg/m^3を記録した。2ヵ月経過後の3月上旬, 東経40度線に沿った北上航路では南緯62度付近で最大値1.17mg/m^3を観測した。 Chlorophyll a concentrations in the surface (by bucket sampling) and subsurface sea waters (by pumping from bottom of ship at ca. 8m depth) were measured along the course of the icebreaker SHIRASE from November 1984 to April 1985,as part of the routine works of marine biology of the 26th Japanese Antarctic Research Expedition (JARE-26). Mean value of the surface chlorophyll a was 0.01mg/m^3 higher than that of the subsurface chlorophyll a. However, the fluctuations of chlorophyll a at both strata showed a similar tendency throughout the cruise. Positive correlation was clearly observed between the surface and the subsurface chlorophyll a. High chlorophyll a concentrations (more than 0.5mg/m^3) were observed in the sea adjacent to Japan, the strait of Malacca and the Southern Ocean. In the Southern Ocean, the chlorophyll a content fluctuated from 0.04mg/m^3 to 1.51mg/m^3. The maximum concentration on the southward leg in early December was 1.51mg/m^3 between the Australasian Subantarctic Front and the Antarctic Convergence. On the other hand, the maximum value on the northward leg in early March was 1.17mg/m^3 near Lat. 62°S. departmental bulletin paper